EVALUASI PENILAIAN KINERJA MTS AL-FALAH: MENGIDENTIFIKASI TINGKAT KUALITAS PENDIDIKAN DAN PRAKTIK BAIK - Nisa Putri Alifia; Siti Sahara; Alya Azzahra; Haifina Qurrotu A; Hanif Arif Setyawan (Jurnal Manajemen Pendidikan, 2026)
Although performance evaluation and curriculum implementation are crucial elements in educational transformation, practices in the field often face obstacles such as educators’ limited technological skills and a lack of innovation in evaluation models tailored to Islamic educational institutions. This study aims to evaluate performance assessment at Madrasah Tsanawiyah Al-Falah to identify the quality of education and identify best practices that can serve as a model for educational quality improvement. The research method employed was a qualitative approach using a case study design, in which data were collected through in-depth interviews, passive participatory observation, and document analysis, which were then analyzed using an interactive model. The results indicate that the quality of education falls into the “good” category as assessed by organizational governance, public relations management, and student services. Key findings reveal the innovation of the Love-Based Curriculum as an internal curriculum integrated with the Merdeka Curriculum to strengthen character education through the values of compassion, empathy, and religiosity. Additionally, best practices were identified in the form of deep, student-centered learning transformation grounded in the pillars of awareness, meaningfulness, and a pleasant atmosphere.